Autophagy Is Rapidly Induced by Salt Stress and Is Required for Salt Tolerance in Arabidopsis - Luo, Liming; Zhang, Pingping; Zhu, Ruihai; Fu, Jing; Su, Jing; Zheng, Jing; Wang, Ziyue; Wang, Dan; Gong, Qingqiu (Frontiers in Plant Science, 2017)
Salinity stress challenges agriculture and food security globally. Upon salt stress, plant growth slows down, nutrients are recycled, osmolytes are produced, and reallocation of Na+ takes place. Since autophagy is a high-throughput degradation pathway that contributes to nutrient remobilization in plants, we explored the involvement of autophagic flux in salt stress response of Arabidopsis with various approaches. Confocal microscopy of GFP-ATG8a in transgenic Arabidopsis showed that autophagosome formation is induced shortly after salt treatment. Immunoblotting of ATG8s and the autophagy receptor NBR1 confirmed that the level of autophagy peaks within 30 minutes of salt stress, and then settles to a new homeostasis in Arabidopsis. Such an induction is absent in mutants defective in autophagy. Within 3 hours of salt treatment, accumulation of oxidized proteins is alleviated in the wild-type; however such a reduction is not seen in in atg2 or atg7. Consistently, the Arabidopsis atg mutants are hypersensitive to both salt and osmotic stresses, and plants overexpressing ATG8 perform better than the wild-type in germination assays. Quantification of compatible osmolytes further confirmed that the autophagic flux contributes to salt stress adaptation. Imaging of intracellular Na+ revealed that autophagy is required for Na+ sequestration in the central vacuole of root cortex cells following salt treatment. These data suggest that rapid protein turnover through autophagy is a prerequisite for salt stress tolerance in Arabidopsis.